Design optimization of microwave absoerbers using waste materials for electromagnetic compatibility applications - Muhammad Nadeem Iqbal (School of Computer and Communication Engineering, University Malaysia Perlis, 2014)
Use of discarded material in value-added products has been a common practice since long. Recently, two wastes have been studied for their potential use in microwave absorber applications. One of these wastes is rice husk (RH) from the paddy fields and is a natural source of carbon, while another is scrap rubber (SR) from discarded automobile tires (a synthetic source of carbon black). The RH has a low bulk density (70-110 kg/mp3s), and thus requires large volumes for storage. Likewise, a very expensive and complex recycling process is required to reuse the synthetic SR. Burning of these wastes, releases a large amount of toxic carbon mono oxide (CO) and carbon dioxide (CO2) gases in the air. Furthermore, commercially available dielectric foam absorbers are specially dipped in a carbon solution (graphite suspension) before, they can be used in anechoic chambers. However, both of the wastes have already lossy carbon contents, which has made them attractive raw materials for the fabrication of the low cost microwave absorbers. In this thesis electromagnetic compatibility (EMC) oriented study of the microwave absorbers composed of these two wastes in planar and geometrically-tapered (GT) hollow shapes is presented. Innovative use of these two wastes, in EMC absorbers can make significant contributions in our efforts to cope with the waste disposal and the problems associated with the environmental pollution. As a first step of the study, the samples were fabricated in composite form by mixing different loadings (wt. %) of these two wastes, with the two types of adhesives i.e., unsaturated polyester resin (UPR) and a commercially available non-toxic glue. The samples were prepared on laboratory scale at room temperature by using one of the easiest composite fabrication methods i.e., hand lay-up method. In the second step, dielectric properties of the samples were measured using an easy to use broadband co-axial sensor over the frequency range of 2 to 20 GHz. These properties were then used, to study and determine the characteristic impedance, wave attenuation constant, phase constant, and depth of penetration of the incident wave in the lossy wastes. Planar microwave absorbers composed of a single layer, impedance-graded two and three-layer designs were studied numerically and experimentally for their effectiveness in suppressing the discrete frequency (narrowband) and broadband electromagnetic echoes. The values of the reflectivity were found to be well below the -20 dB at discrete frequencies with narrowband performance, in case of single layer absorbers. Broadband performance below -15 dB was achieved by using impedance-gradient design. The GT hollow absorbers were studied to solve the issues related to the installation of the bulky solid absorbers. These absorbers were designed on the basis of the wave attenuation and depth of penetration data and their EMC performance was evaluated in terms of bi-static reflectivity performance. The results proved that, while, these absorbers had 58% less weight and 15% less height than the solid absorbers, they provided standard performance, i.e., < -20 dB. The optimum value of the weight fraction of the RH for hollow absorbers was found to be in the range of 35 to 60 %, of the overall composite, for which less structural damage was observed. The performance of the absorbers was found to be below -10 dB even at 100 C in the X band of frequencies. A two-layer pyramidal design based on the cladding concept was also studied to improve the low frequency EMC performance of the solid absorbers composed of scrap rubber from automobile tires.